2019
DOI: 10.1182/bloodadvances.2018028316
|View full text |Cite
|
Sign up to set email alerts
|

A genomics-informed computational biology platform prospectively predicts treatment responses in AML and MDS patients

Abstract: Patients with myelodysplastic syndromes (MDS) or acute myeloid leukemia (AML) are generally older and have more comorbidities. Therefore, identifying personalized treatment options for each patient early and accurately is essential. To address this, we developed a computational biology modeling (CBM) and digital drug simulation platform that relies on somatic gene mutations and gene CNVs found in malignant cells of individual patients. Drug treatment simulations based on unique patient-specific disease network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Ex vivo DSS will likely synergize with genomic data and emerging precision medicine approaches such as in silico computational biology modeling. 47,48 Combining both genomics-based and ex vivo functional data may further refine precision therapy, enhance the selection of rational drug combinations, and ultimately improve outcomes for patients with myeloid neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo DSS will likely synergize with genomic data and emerging precision medicine approaches such as in silico computational biology modeling. 47,48 Combining both genomics-based and ex vivo functional data may further refine precision therapy, enhance the selection of rational drug combinations, and ultimately improve outcomes for patients with myeloid neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytogenetic data is far more limited with great heterogeneity which should be carefully interpreted. Recently, with the increased access to gene mutation landscape, genetic counseling for both patients and their families would affect pediatric MDS's clinical diagnosis and therapeutic decision s [36][37][38]. The gene mutation assay was performed among the 16 patients of this cohort and 14 of them were verified to carry different gene mutations (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mutations in TET2 have previously been associated with responses to HMAs in MDS, or in AML with 20–30% blasts [ 7 , 21 ]. Likewise, via a genomics-informed computation biology platform recently developed to predict responses to HMAs in 18 patients with MDS/AML, the authors found that gain-of-function mutations in EZH2 and IDH1 / 2 were predictors of the response to the CpG-methylating effects of azacytidine via DNMT1 inhibition [ 22 ]. In contrast to our data, Jung and colleagues found that U2AF1 mutation was significantly associated with non-response to azacytidine in patients with MDS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%